Prevalence of Lung Cancer with a History of Tuberculosis - Nadira Putri Nastiti; Laksmi Wulandari; Sulistiawati Sulistiawati; Anna Febriani; Wiwin Is Effendi (Jurnal Respirasi, 2023)
Introduction: Lung cancer ranks as the second most common diagnosis of malignancy cases in the world with the highest mortality, while Indonesia is the country with the largest tuberculosis (TB) burden after India. Although these two diseases have a high incidence and mortality rate and are one of the main causes of health problems, coexistence between these two diseases is very rare. A similar clinical and radiological feature complicates the diagnosis and worsens the prognosis. This study aimed to determine the prevalence and distribution patterns of lung cancer incidence with a history of TB. Methods: This was a descriptive study. The data were obtained retrospectively from the electronic medical records of lung cancer patients from one roof oncology clinic, Dr. Soetomo General Hospital, Surabaya, in 2018–2020, meeting the inclusion and exclusion criteria. Results: Specifically, 76 out of 1,044 (7.3%) lung cancer patients had a history of TB, with the distribution being men (71.1%), in an age range of 50-59 years old (34.2%), who were active smokers (36.9%), had an adenocarcinoma type of cancer (90.8%), had a positive EGFR gene mutation (50%), and had a diagnosis of non–small cell lung cancer (NSCLC) during stage IV (79%) after a TB diagnosis (54%) with a time interval of 1 or >10 years. Conclusion: The prevalence of lung cancer with a history of TB was 7.3%. Lung cancer screening is important in TB patients after one or even >10 years of diagnosis to reduce the morbidity and mortality rates because of this risk of coexistence.